Tectono-stratigraphy of the Eocene Zhu-1 Sub-basin in the Pearl River Mouth basin, China: controls on hydrocarbon source rock variability and implications - Liu, Pei; Peng, Guangrong; Luo, Ming; Wang, Yuchen; Xiong, Wanlin; Song, Penglin; Wu, Guanyun (Frontiers in Earth Science, 2025)
In rift basins, the vertical development and distribution of hydrocarbon source rocks show a makeable variability tightly linking to the tectono-stratigraphic interaction and evolution. This is also highly focused for petroleum industry, which is posing challenges for systematic hydrocarbon accumulation patterns. In the Zhu-1 Sub-basin of the Pearl River Mouth basin, the Eocene rift-related strata are important intervals for potential hydrocarbon exploration. This study analyzes the temporal and spatial attributes caused by tectonic transitions using 3D-seismic, drilling and logging well, and geochemical data, uncovering the impact of tectonic transition on the formation and development of hydrocarbon source rocks in the Eocene rift-related strata in the Zhu-1 Sub-basin. The results indicate that tectonic transitions caused by the HZ movement (∼43 Ma) have affected the migration of the centers of depocenter and subsidence and drove the formation of two main hydrocarbon source rocks in the upper and lower sections of the Wenchang Formation. The migration of rifting activity has influenced the lateral distribution of high-abundance dark high-quality hydrocarbon source rocks, and expand the range of high-quality hydrocarbon source rocks. The half-graden styles in the different sag change associated with tectonic transitions, and basement uplift and magmatic bottoming reshape the internal stratigraphic structure of the half-graden, leading to the variability of hydrocarbon accumulations. The proposed three hydrocarbon distribution modes, gentle slope dominant, steep-slope dominant and double-slope dominant, were developed in different sags. These models provide important geological theoretical support for the search of potential large-scale hydrocarbon reservoirs in the Pearl River Mouth basin, South China Sea.